Assessment of physical fitness of 12-year-old elementary children in Sumenep district through Tes Kebugaran Pelajar Nusantara (TKPN) - Ainur Rasyid; Winda Nuraisyah; Abdul Azis; Moh. Junaidi; Nugroho Agung Supriyanto (Physical Education Departement of University PGRI Jombang, 2025)
Physical fitness in primary school children is an important aspect in supporting physical development and long-term health. This study aimed to evaluate the physical fitness level of 12-year-old students in Sumenep district using TKPN. This study was conducted in a descriptive quantitative manner involving 134 students selected through purposive sampling. The research instruments included measurements of Body Mass Index (BMI), V Sit and Reach, Sit-ups, Squat Thrust, and Progressive Aerobic Cardiovascular Endurance Run (PACER) Test. The data obtained were analyzed descriptively based on the physical fitness categories established by TKPN. The results showed that the majority of students were at a low level of physical fitness. A total of 83% of students had a low level of cardiorespiratory endurance based on the PACER test results, while 75% of students showed low muscle strength in the Squat Thrust test. In addition, 69% of students had poor abdominal muscle strength on the Sit-up test, and 56% of students showed low flexibility on the V Sit and Reach test. No students achieved the “Good” or “Excellent” category in the overall physical fitness components measured. Based on the results of the study, it was concluded that although 72% of students fell into the undernourished category based on Body Mass Index (BMI), this was not matched by an adequate level of physical fitness, where only 2.5% of students were in the sufficient category. Therefore, it can be concluded that the application of TKPN to students at SDN Pajagalan 1, SDN Kepanjin, SDN Karangduak 2 and SDN Bangselok in Kota Sumenep Sub-district, East Java Province, overall shows a level of physical fitness that is in the moderate category.